PENGEMBANGAN MEDIA MONOPOLI BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN KECERDASAN EMOSIONAL - Nina Nabila; Evi Afiati; Siti Muhibah (STKIP Subang, 2026)
This study aims to develop monopoly game media to enhance emotional intelligence based on Problem Based Learning. This research is based on the low emotional intelligence of grade XI students at SMAN 9 Tangerang Regency. The research method used is research and development (R&D) with the ADDIE model. The results of this study indicate that the emotional intelligence monopoly game media is feasible to use, supported by the media feasibility test results which obtained an average score of 87.2% with the category